Exploring Distressed Cashew‐Nut Farmland Rentals Among Ethnic Groups in Binh Phuoc Province, Vietnam. (22nd November 2021) - Nguyen, Toai; Lawler, Susan; Paul, Warren
Abstract: Remote communities alleviate economic hardship by renting their crops to others, and these transactions are often informal and exploitative. Because farmland is an important income source for rural areas, understanding the participation in distress rentals of cashew nut farms is critical for sustainable development. Previous studies have highlighted relationships between socioeconomic factors and participation in land rentals but have failed to examine distress rentals under ethnic contexts. In this study, we interviewed 121 villagers to examine socioeconomic determinants of the participation in distress rentals of farmers with regard to their indigenous culture in two communes in Binh Phuoc province. We found that ethnic identity, land‐ownership, informal training in agriculture, family size, and proximity to markets are statistically significant in explaining the likelihood to participate in distress rentals. Based on these findings, we make several recommendations for how local governments can create better policies to ensure social justice.